One-Step Salvage of Infected Prosthetic Breast Reconstructions Using Antibiotic-Impregnated Polymethylmethacrylate Plates and Concurrent Tissue Expander Exchange. Issue 3 (September 2016) - Albright, Steven B.; Xue, Amy S.; McKnight, Aisha; Wolfswinkel, Erik M.; Hollier, Larry H.; Brown, Rodger H.; Bullocks, Jamal M.; Izaddoost, Shayan A.
Abstract : Purpose: Periprosthetic infection represents a major complication in breast reconstruction, frequently leading to expander-implant loss. Recent studies report variable success in the salvage of infected breast prostheses through systemic antibiotic therapy and surgical intervention. There is currently no consensus regarding a management algorithm for attempted salvage. The purpose of this pilot study was to evaluate the early outcomes of a protocol using antibiotic-impregnated polymethylmethacrylate (PMMA) implant placement with expander device exchange. Methods: A retrospective database was queried to identify all patients with infected implant-based breast reconstruction who were treated by the study authors and who underwent attempted salvage under the study protocol. All patients received intravenous antibiotics followed by surgical debridement of the infected pocket, insertion of antibiotic-impregnated PMMA plates and/or beads, device exchange, and postoperative antibiotics. After clinical resolution of infection, tissue expansion was performed with the PMMA implants remaining in situ until exchanged to permanent implants. Results: All patients with infected prosthetic breast reconstructions achieved implant pocket sterilization using this method. At a mean follow-up of 8.2 months (range, 1–19 months), none of these patients have required reoperation for capsular contracture. One patient, while under treatment with prednisone for a rash, developed recurrent infection, which led to explantation of her implant. Two patients underwent radiation therapy while an antibiotic plate and tissue expander were in place, with no observed exposure or infection recurrence. Conclusions: Sustained local antibiotic delivery using PMMA implants and expander device exchange can successfully salvage an infected breast implant. Perceived benefits include shorter time to completed reconstruction, preserved skin envelope integrity, and possibly improved long-term aesthetic outcomes.